2014
DOI: 10.1007/s10517-014-2413-4
|View full text |Cite
|
Sign up to set email alerts
|

System of Matrix Metalloproteinases and Cytokine Secretion in Type 2 Diabetes Mellitus and Impaired Carbohydrate Tolerance Associated with Arterial Hypertension

Abstract: The study included patients with type 2 diabetes mellitus and impaired carbohydrate tolerance associated with arterial hypertension, patients with arterial hypertension, and healthy volunteers. We evaluated the levels of matrix metalloproteinases 2 and 9 (MMP-2, MMP-9), tissue inhibitor of metalloproteinase type 1 (TIMP-1), glucose, insulin, C-peptide, glycated hemoglobin, and spontaneous and mitogen-activated cytokine secretion (IL-2, IL4, IL-6, IL-10, IL-17, TNF-α, and IFN-γ). Patients with type 2 diabetes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…However, healthy subjects were not enrolled and circulating Th17 levels were not measured in this study [7]. Consistent with these results, many clinical studies have found that circulating IL-17 levels significantly increased in hypertensive patients [13, 14]. Moreover, Yao et al found that serum IL-17 levels were significantly higher in subjects with prehypertension, defined as systolic BP of 120 to 139 mm Hg or diastolic BP of 80 to 89 mm Hg, than in subjects with optimal BP, defined as systolic BP < 120 mm Hg and diastolic BP < 80 mm Hg [31].…”
Section: Discussionsupporting
confidence: 60%
“…However, healthy subjects were not enrolled and circulating Th17 levels were not measured in this study [7]. Consistent with these results, many clinical studies have found that circulating IL-17 levels significantly increased in hypertensive patients [13, 14]. Moreover, Yao et al found that serum IL-17 levels were significantly higher in subjects with prehypertension, defined as systolic BP of 120 to 139 mm Hg or diastolic BP of 80 to 89 mm Hg, than in subjects with optimal BP, defined as systolic BP < 120 mm Hg and diastolic BP < 80 mm Hg [31].…”
Section: Discussionsupporting
confidence: 60%
“…The study reported inflammatory cytokines disorder was used as critical early biomarkers for estimating the T2DM risks and complications 47,48. T2DM patients had significantly higher levels of inflammatory markers interleukin-1B (IL-1B) and IL-6, while IL-10 showed lower levels, compared with non-diabetic patients 47,49. STAT1 is highly expressed in patients with T2DM.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that inflammatory cytokines are elevated in patients with T2D. For example, IL-17, which was reported to suppress differentiation of preadipocytes and impair adipsin expression in adipocytes [25], was elevated in patients with T2D [26, 27]. Furthermore, IL-17 has been associated with insulin resistance in animal models [28].…”
Section: Discussionmentioning
confidence: 99%